2022
DOI: 10.1097/md.0000000000031455
|View full text |Cite
|
Sign up to set email alerts
|

Rare finding of duodenal lymphangioma in a patient with Helicobacter pylori associated gastritis: A case report

Abstract: Rationale: Lymphangiomas are lymphatic malformations most commonly found in the head, neck and axilla. Their incidence in gastrointestinal tract, especially duodenum is very rare. They are mostly congenital and are usually seen in children. Owing to their asymptomatic nature, these tumors are often diagnosed incidentally. Surgical resection is the definite treatment. Patient concerns: We represent a case of a 30-year-old male with duodenal lymphangioma with presentation of intermittent dyspepsia for 1 year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…Our results showed that lymphoscintigraphy not only confirmed chylothorax in most patients but also found extra thorax lymphatic system lesions. Such example is lymphangiomas, which are rare, benign lymphatic pathological change that arise due to the failure of the individual lymphatic tissues to connect with the general lymphatic system, and may or may not communicate with the rest of the system [36][37][38]. In our study, 99m Tc-DX lymphoscintigraphy did not find as many lesions as reported in the literature [39].…”
Section: Discussionsupporting
confidence: 45%
“…Our results showed that lymphoscintigraphy not only confirmed chylothorax in most patients but also found extra thorax lymphatic system lesions. Such example is lymphangiomas, which are rare, benign lymphatic pathological change that arise due to the failure of the individual lymphatic tissues to connect with the general lymphatic system, and may or may not communicate with the rest of the system [36][37][38]. In our study, 99m Tc-DX lymphoscintigraphy did not find as many lesions as reported in the literature [39].…”
Section: Discussionsupporting
confidence: 45%